PROBLEMS OF DIGITALIZATION AND EDUCATION QUALITY IN THE MODERN EDUCATION SYSTEM. (Universal International Scientific Journal, 2026)
Improving the quality and efficiency of education in the process of introducing digital technologies into the modern education system is one of the most pressing issues in the education system of Uzbekistan and the world today.
Keywords: digitalization problems, quality of education, modern education system, digital technologies, information and communication technologies, online education, distance learning, digital literacy, teaching effectiveness, innovations in education, pedagogical technologies, teacher competence, student activity, digitalization of the educational process, internet resources, inequality in education, technical infrastructure, information security, quality of knowledge, assessment system